Pengaruh Influencer Marketing dan Kualitas Produk terhadap Keputusan Pembelian Produk Erigo Apparel - Gayoe Angger Arhofa; Sonja Andarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to identify and determine the effect of influencer marketing and product quality on the purchasing decision of Erigo Apparel products. This study uses quantitative methods by distributing questionnaires to 100 people. The population in this study was respondents who had active social media accounts as well as followers of Erigo Apparel social media accounts and respondents had bought and used Erigo Apparel products. The data analysis method used is multiple linear regression using SPSS 25 for Windows. This test uses two independent variables, namely influencer marketing, product quality and purchasing decisions as dependent variables. The results of this study are 1) Influencer marketing and product quality simultaneously affect the decision to purchase Erigo Apparel products. 2) Influencer marketing partially influences the decision to purchase Erigo Apparel products. 3) Product quality partially influences the decision to purchase Erigo Apparel products. Keywords: Influencer Marketing, Product Quality, Purchase Decisions